Significance of the Extent of Intestinal Resection on the Outcome of a Short-bowel Syndrome in a Porcine Model. (2nd January 2016) - Frongia, Giovanni; Nickkholgh, Arash; Hafezi M, Mohammad Reza; Arvin, Jalal; Saffari, Arash; Golriz, Mohammad; Aydin, Esvad; Weih, Sandra; Kessler, Markus; Emami, Golnaz; Garoussi, Camelia; Okun, Jürgen G.; et al.
ABSTRACT: Aim of the study: Insufficient data are available to determine the most suitable extent of intestinal resection required to induce short-bowel syndrome (SBS) in pigs. This study aimed to compare the three main SBS-models published. Methods: A 75%, 90%, or 100% mid-intestinal resection was performed in groups of n = 5 pigs each. Clinical (body weight, stool consistency) and biochemical (serum eletrolytes, citrulline, albumin, prealbumin, and transferrin) parameters were determined daily, functional (D-xylose resorption) and histological (intestinal villus length) parameters were determined after 2 weeks. A t -test and ANOVA were used for statistical analysis. Results: Only in the 100% group, we observed a persistent weight loss (13.6 ± 3.8%) and diarrhea, as well as a decrease in prealbumin-levels (41%) and transferrin levels (33%). Serum electrolytes remained stable in all groups during the observation period. Citrulline stabilized at different levels (100% group 13.9 ± 1.0 μmol/L; 90% group 18.8 ± 1.0 μmol/L; 75% group 26.3 ± 1.4 μmol/L; all p < .05). D-xylose resorption was lowest in the 100%, followed by 90% and 75% group (100% group 32.8 ± 4.9 mg/L; 90% group 50.0 ± 19.6 mg/L; 75% group 57.8 ± 8.8 mg/L; p = .393). Intestinal villus length decreased in all groups (100% group 11.0%; 90% group 14.0%; 75% group 19.1%). Conclusions: 75% intestinal resection is less suitable as an SBS model, as animals tend to recover remarkably. The 90% model is suitable for longer-term studies, as animals might survive longer due to partial compensation. Due to severe nutritional, biochemical, and physiological derangements, the 100% model can only be used for acute experiments and those immediately followed by small bowel transplantation.